Characteristics and main clinical outcomes of patients undergoing transtibial amputation - de Souza, Silvio Renato Silva; Mansur, Henrique; Pinto, Zaira Reinaldo de Sousa Moreira; Castro Júnior, Isnar Moreira (Scientific Journal of the Foot & Ankle, 2018)
Objective: To analyse the epidemiological profile of patients undergoing transtibial amputation (TTA) of the lower limb, including the prosthetic fitting rate, the degree of patient satisfaction, and postoperative complications. Methods: This retrospective study was designed to analyse the epidemiological profile of patients undergoing TTA from 2012 through 2016. Prosthetic fitting rate, degree of satisfaction, and postoperative complications were analysed. Results: The sample included 68 patients, of whom 42 were male (62.7%), with a mean age of 50.3 years. Of the participants, 61.2% had finished elementary school only, and 46.2% were white. The most common reason for amputation was chronic osteomyelitis, which was present in 53.7% of participants. A prosthesis was fitted in 89.6% of patients, with most (78.3%) adapting to it well. Of the participants, 40.3% experienced postoperative complications, and mortality was 21.9%. Regarding satisfaction, 76.1% of patients were not satisfied with the surgical outcome. Conclusion: Patients who underwent TTA were most commonly white males of approximately 50 years of age; the most prevalent comorbidities were systemic arterial hypertension and diabetes mellitus, and the most frequent reason for amputation was chronic osteomyelitis. Patient dissatisfaction was significantly associated with age (>60 years old) and depression. The prosthetic fitting rate and adaptation to the prosthesis were directly related to patient satisfaction. Level of Evidence IV; Therapeutic Studies; Case Series.